Prestroke antiplatelet therapy and early prognosis in stroke patients: the Dijon Stroke Registry. Issue 6 (24th December 2012) - Béjot, Y.; Aboa‐Eboulé, C.; de, E.; Jacquin, A.; Troisgros, O.; Hervieu, M.; Osseby, G. V.; Rouaud, O.; Giroud, M.
<x xml:space="preserve">Abstract</x> Background and purpose Previous antiplatelet therapy (APT) in cardiovascular prevention is common in patients with first‐ever stroke. We aimed to evaluate the prognostic value of APT on early outcome in stroke patients. Methods All first‐ever strokes from 1985 to 2011 were identified from the population‐based Stroke Registry of Dijon, France. Demographic features, risk factors, prestroke treatments and clinical information were recorded. Multivariate analyses were performed to evaluate the associations between pre‐admission APT and both severe handicap at discharge, and mortality at 1 month and 1 year. Results Among the 4275 patients, 870 (20.4%) were previously treated with APT. Severe handicap at discharge was noted in 233 (26.8%) APT users and in 974 (28.7%) non‐users. Prestroke APT use was associated with lower odds of severe handicap at discharge [adjusted odds ratio (OR): 0.79; 95% confidence interval (CI): 063–1.00; P = 0.046], non‐significant better survival at 1 month [adjusted hazard ratio (HR): 0.87; 95% CI: 0.70–1.09; P = 0.222] and no effect on 1‐year mortality (HR: 0.94; 95% CI 0.80–1.10; P = 0.429). In stratum‐specific analyses, APT was associated with a lower risk of 1‐month mortality in patients with cardioembolic ischaemic stroke (HR: 0.65; 95% CI: 0.43–0.98; P = 0.040). Conclusions APT before stroke was associated with less severe handicap at discharge, with no significant protective effect for mortality at 1 month except in patients with cardioembolic stroke. No protective effect of APT was observed for mortality at 1 year. Further studies are needed to understand the mechanisms underlying the distinct effects of prior APT observed across the ischaemic stroke subtypes.